Dynamic policy interactions in a monetary union - Carlberg, Michael (Springer eBooks., 2011)
This book studies the dynamics of monetary and fiscal interactions in the Euro Area. The policy makers are the European Central Bank and national governments. The primary target of the ECB is low inflation. And the primary target of a national government is low unemployment. However, there is a short-run trade-off between low inflation and low unemployment. Here the main focus is on sequential policy decisions. Another focus is on simultaneous and independent policy decisions. And a third focus is on policy cooperation. There are demand shocks, supply shocks, and mixed shocks. There are country-specific shocks and common shocks. The key question is: Given a shock, what are the dynamic characteristics of the resulting process?